Morphological Associations between the Distal Radioulnar Joint and the Lunate - Mauler, Flavien; Beaulieu, Jean-Yves (Journal of Wrist Surgery, 2018)
Background Variations in morphology of the carpal bones have been described. Their implication in wrist disease and specific kinematic features has been recognized, and a better knowledge of these variations is essential.Questions/Purpose To radiographically determine any association between the morphological variations of the distal radioulnar joint (DRUJ) and the lunate bone.Materials and Methods Radiographs of 100 wrists of patients presenting to the emergency department with wrist pain and referred to our outpatient clinic were retrospectively reviewed for DRUJ inclination, ulnar variance, and radiocarpal and midcarpal morphology of the lunate.Results There were 51 females and 49 males, mean age 51.2 years (range: 21–94). There was a statistically significant association between the DRUJ inclination and the morphology of the radiocarpal side of the lunate (p < 0.001). The mean values of ulnar variance changed according to DRUJ inclination and the radiocarpal side of the lunate (p < 0.001) but not according to the midcarpal side of the lunate. There was no significant association between the morphology of the DRUJ and the midcarpal side of the lunate or between the midcarpal and the radiocarpal morphology of the lunate.Conclusion This study demonstrated a statistically significant association at the radiocarpal level between the DRUJ inclination, ulnar variance, and the morphology of the lunate. No association was found with the morphology of the midcarpal side of the lunate. Accordingly, a classification of these carpal associations is proposed, highlighting seven main wrist configurations.Clinical Relevance These associations can guide future studies of wrist kinematics.
Keywords: carpal anatomy; morphology variations; distal radioulnar joint; lunate